The relationship of plasma Trans fatty acids with dietary inflammatory index among US adults - Mazidi, Mohsen (Lipids Health Dis, 2017)
BACKGROUND: It has been suggested that trans fatty acids (TFAs) play an important role in cardiovascular diseases. We investigated the association between plasma TFAs and the dietary inflammatory index (DII) ™ in US adults. METHODS: National Health and Nutrition Examination Survey (NHANES) participants with data on plasma TFAs measured from 1999 to 2010 were included. Energy-adjusted-DII ™ (E-DII ™) expressed per 1000 kcal was calculated from 24-h dietary recalls. All statistical analyses accounted for the survey design and sample weights. RESULTS: Of the 5446 eligible participants, 46.8% (n = 2550) were men. The mean age of the population was 47.1 years overall, 47.8 years for men and 46.5 years for women (p = 0.09). After adjustment for C-reactive protein, body-mass-index, smoking, race, age, education, and marital status in linear regressions, trans 9-hexadecenoic acid [β coefficient 0.068 (95% CI: 0.032 to 0.188)], trans 11-octadecenoic acid [β coefficient 0.143 (95% CI: 0.155 to 0.310)], trans 9-octadecenoic acid [β coefficient 0.122 (95% CI: 0.120 to 0.277)], trans 9, and trans 12-octadienoic acid [β coefficient 0.103 (95% CI: 0.090 to 0.247)] were positively associated with the DII (all p < 0.001). CONCLUSION: The association of plasma TFAs with a marker of dietary inflammation suggests an underlying mechanism in the initiation and progression of cardiovascular diseases.